2007
DOI: 10.1007/s11010-007-9428-3
|View full text |Cite
|
Sign up to set email alerts
|

Altered structure and deregulated expression of the tumor suppressor gene retinoblastoma (RB1) in human brain tumors

Abstract: A total of 40 human brain tumor samples were analyzed for tumor-specific alterations at the RB1 gene locus. Gliomas were more prevalent in younger males and meningiomas in older females. Southern blot analysis revealed loss of heterozygosity (LOH) at the intron 1 locus of RB1 gene in 19.4% of informative cases and this is the first report showing LOH at this locus in human brain tumors. Levels of RB1 mRNA and protein, pRb, and the percentage of hyperphosphorylated form of pRb were also analyzed in these tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…) and minimal signal using phospho‐RB1‐specific antibodies (Figs 7 and ). In contrast, elevated expression of hyperphosphorylated RB1, or loss/inactivation of RB1, has been described in most human glioma samples . Recent studies have suggested a more complex role for RB1 family proteins with RB1 acting as a molecular adaptor at the crossroads of multiple pathways, depending on cellular context .…”
Section: Discussionmentioning
confidence: 58%
“…) and minimal signal using phospho‐RB1‐specific antibodies (Figs 7 and ). In contrast, elevated expression of hyperphosphorylated RB1, or loss/inactivation of RB1, has been described in most human glioma samples . Recent studies have suggested a more complex role for RB1 family proteins with RB1 acting as a molecular adaptor at the crossroads of multiple pathways, depending on cellular context .…”
Section: Discussionmentioning
confidence: 58%
“…U87dEGFR cells have a wild-type p53 gene with EGFRvIII expression and inactivation of p16 and PTEN. Consistent with this deregulation, these cells have an increase in the level of total pRb protein and mostly in the hyperphosphorylated form (31,32), which leads to release of E2F-1 and stimulates cells to bypass the G 0 -G 1 checkpoint and enter into S phase. However, this unscheduled entry into S phase can trigger apoptosis when deregulated E2F-1 activity reaches a certain threshold induced by an DNA-damaging agent (33).…”
Section: Discussionmentioning
confidence: 88%
“…It has been identified to be related with a variety of human cancers including brain tumors [22]. Mathivanan et al found loss of heterozygosity and deregulated expression of RB1 in human brain tumors [23].
Fig.
…”
Section: Resultsmentioning
confidence: 99%